Benefit-risk profile of extended dual antiplatelet therapy beyond 1 year in patients with high risk of ischemic or bleeding events after PCI. (19th May 2021) - Wang, Hao-Yu; Gao, Run-Lin; Xu, Bo; Yang, Yue-Jin; Yin, Dong; Wang, Yang; Dou, Ke-Fei
Abstract: The benefits and harms of dual antiplatelet therapy (DAPT) continuation with aspirin and clopidogrel beyond 1 year after percutaneous coronary intervention (PCI) with drug-eluting stent (DES) implantation for high ischemic or bleeding risk patients remain unclear. All consecutive patients undergoing PCI were prospectively included in the Fuwai PCI Registry from January 2013 to December 2013. We evaluated 7521 patients who were at high risk for thrombotic or hemorrhagic complications and were events free at 1 year after the index procedure. "TWILIGHT-like" patients with high risk of bleeding or ischemic events were defined by clinical and angiographic criteria. The primary ischemic outcome was major adverse cardiac and cerebrovascular events [MACCE] (a composite of all-cause death, myocardial infarction, or stroke). Median follow-up duration was 2.4 years. The risk of MACCE was significantly lower in DAPT>1-year group (n = 5252) than DAPT≤1-year group (n = 2269) (1.5% vs. 3.8%; hazard ratio [HR]: 0.37; 95% confidence interval [CI]: 0.27–0.50; P < .001). This difference was largely driven by a lower risk of all-cause death. In contrast, the risk of Bleeding Academic Research Consortium (BARC) type 2, 3 or 5 bleeding was statistically similar between the two groups (1.0% vs. 1.1%; HR: 0.80; 95% CI: 0.50–1.28; P = .346). Results were consistent after multivariable regression and propensity-score matching. Prolonged DAPT beyond 1 year after DES implantation resulted in a significantly lower rate of atherothrombotic events, including a mortality benefit, with no higher risk of clinically relevant bleeding in "TWILIGHT-like" patients who were at high-risk for ischemic or bleeding events.